Dapagliflozin a glucose‐regulating drug with diuretic properties in subjects with type 2 diabetes. Issue 9 (5th June 2013) - Lambers Heerspink, H. J.; de Zeeuw, D.; Wie, L.; Leslie, B.; List, J.
Abstract Aims Sodium–glucose co‐transporter 2 (SGLT2) reabsorbs glucose and sodium in the renal proximal tubule. Dapagliflozin, an SGLT2 inhibitor, targets hyperglycaemia in type 2 diabetes by increasing renal glucose excretion. To investigate whether the parallel occurring sodium loss would have diuretic‐like physiologic effects, we compared dapagliflozin and hydrochlorothiazide (HCTZ) effects on 24‐h blood pressure (BP), body weight, plasma volume and glomerular filtration rate (GFR). Methods In this randomized, placebo‐controlled, double‐blind trial, 75 subjects with type 2 diabetes were assigned placebo, dapagliflozin 10 mg/day, or HCTZ 25 mg/day. Changes from baseline BP, body weight, plasma volume and GFR were assessed after 12 weeks of treatment. Results Subjects' mean age was 56 years, type 2 diabetes mellitus (T2DM) duration 6.3 years, and haemoglobin A1c (HbA1c) 7.5%. Treatment with placebo, dapagliflozin or HCTZ resulted in changes from baseline in 24‐h ambulatory mean systolic blood pressure (SBP) of −0.9 (95%CI −4.2, +2.4), −3.3 (95%CI −6.8, +0.2), and −6.6 (95%CI −9.9, −3.2) mmHg, respectively at week 12, adjusted for baseline SBP. Body weight decreased with dapagliflozin and HCTZ. In a sub‐study plasma volume appeared to decrease with dapagliflozin but did not change with placebo or HCTZ treatment. Dapagliflozin induced a greater reduction in GFR (−10.8%; 95%CI −14.6, −6.7) relative to placebo (−2.9%; 95% CI −6.9, +1.2) or HCTZ (−3.4%; 95%CI −7.3, +0.6). Conclusions Dapagliflozin‐induced SGLT2 inhibition for 12 weeks is associated with reductions in 24‐h BP, body weight, GFR and possibly plasma volume. Cumulatively, these effects suggest that dapagliflozin may have a diuretic‐like capacity to lower BP in addition to beneficial effects on glycaemic control.